Regulation of a glutamine amidotransferase subunit from Bacillus subtilis by a cloned trpE gene from Bacillus pumilus. - Kane, J F (1980)
The influence of a cloned trpE (trpE+p) gene from Bacillus pumilus on the expression of the gat locus in Bacillus subtilis was examined. The trpE gene was regulated by tryptophan and the mtr locus, which specifies the presumed aporepressor. The specific activity of subunit G varied directly with the level of subunit Ep, and the heterologous EpG complex that was formed was stable to gel filtration.